Dynamic regulation and key roles of ribonucleic acid methylation - Zou, Jia; Liu, Hui; Tan, Wei; Chen, Yi-qi; Dong, Jing; Bai, Shu-yuan; Wu, Zhao-xia; Zeng, Yan (Frontiers in Cellular Neuroscience, 2022)
Ribonucleic acid (RNA) methylation is the most abundant modification in biological systems, accounting for 60% of all RNA modifications, and affects multiple aspects of RNA (including mRNAs, tRNAs, rRNAs, microRNAs and long non‑coding RNAs). Dysregulation of RNA methylation causes many developmental diseases through various mechanisms mediated by N6-methyladenosine (m6A), 5-methylcytosine (m5C), N1-methyladenine (m1A), 5-hydroxymethylcytosine (hm5C), and pseudouridine (Ψ). The emerging tools of RNA methylation can be used as diagnostic, preventive, and therapeutic markers. Here, we review the accumulated discoveries to date regarding the biological function and dynamic regulation of RNA methylation/modification to provide new ideas for growth and development.